Yiddishland: a promise of belonging. Issue 2 (3rd April 2021) - Gal-Ed, Efrat
ABSTRACT: Modernist Yiddish literature was an important part of the Yiddish-cultural response to the existential turmoil caused by the First World War. This "small literature, " to use Kafka's phrase, came into being without the support of a nation-state and in an alien environment. In a 1922 edition of Warsaw's avant-garde magazine Albatros, Yiddish poets reflected on their "wandering through various centres of their Jewish extraterritoriality." Five years later, in 1927, when stateless Yiddish literature became a member of the International PEN Club, this existential extraterritoriality underwent a bold reinterpretation with the new concept of "Yiddishland." My paper reconstructs the discourse that led to the transformation of the existential concept of eksteritoryalishkayt along with the creation of the cosmopolitan cultural project originally called " dos land yidish, " and later "Yiddishland:" a republic of words that unified the Yiddish speakers globally via literature and arts.